Highly accurate approximation for sheath currents in high-voltage three-phase cable line - Tkachenko, O.; Pyrohova, U.; Grinchenko, V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2026)
Introduction. This study focuses on sheath currents in high-voltage single-core XLPE-insulated power cables with solid bonding. The analysis covers flat and trefoil three-phase cable lines. Sheath current calculation is essential for evaluating thermal conditions, losses, and overall cable performance. Problem. The regulatory documents of the Ministry of Energy of Ukraine provide formulas for sheath currents. We examine them by comparing with verified analytical solutions and find significant discrepancies in a wide range of typical parameters of high-voltage three-phase cable line. So the formulas in the current regulatory document have a narrow range of applicability, and the engineering calculations based on them may lead to significant inaccuracies and incorrect decisions. Goal. The paper aims to develop novel formulas for the RMS values of sheath currents in high-voltage three-phase cable lines with flat and trefoil arrangements of power cables, ensuring the accuracy required for engineering calculations across a wide range of cable line parameters. Methodology. This study is grounded on the previously developed and experimentally verified analytical model and corresponding formulas for calculating sheath currents and cable line magnetic field. These verified formulas for sheath currents are too cumbersome, so an approximation technique is used to find compact ones. Results. A novel approximation for sheath current in the flat cable line is developed. The discrepancy between the approximation and the verified formulas is within 5 %. Additionally, a new form of the formula for sheath current in the trefoil cable line is proposed. Scientific novelty. To perform the approximation, an original quality index is proposed. It is derived from the heat output of metal sheaths of cables. Practical value. The developed approximation for sheath current can be directly applied to the design of high-voltage cable lines, the analysis of the operating modes, and the control of the compliance of existing cable lines with actual operating conditions. References 20, table 1, figures 4.